TRANSLATION ERRORS AND THEIR CAUSES (KONFERENSIYA, 2025)
This article explores the major types of translation errors and the linguistic, cultural, and pragmatic factors that cause them. Through examples from English–Uzbek translation practice, the study highlights how inadequate linguistic knowledge, cultural mismatches, stylistic inconsistencies, and translator interference lead to inaccurate translations. Methods used in the research include textual analysis, comparison of originals with translated versions, and classification of error types. The article concludes with recommendations for improving translation quality